A Thermodynamical Approach of Chemical Vapour Deposition of TiN on Stainless Steel - Staia. Mariana H. (The Minerals, Metals and Materials Society, 1995)
Thermochemical equilibria of the heterogeneous system Ti-N-H-CI-Fe-Cr-Mo-Ni-Mn-C were calculated by using a commercial software based on the minimization of the free energy. Equilibrium calculations were done for temperatures varying between 800" and l 100°C and an initial molar relationship between reactants, a=NJTiCI,, of 0.1 to 2. The deposition process was considered to occur at atmospheric pressure. The activities of the alloying elements of the stainless steel were considered equal to their molar fractions. It was shown that for the conditions studied the substrate is no inert with respect to the gaseous phase. The existence of liquid chlorides was predicted for temperatures between 800" and 850°C and a ratio between 0.3 and 0.9. The most important metallic chlorides which appears to be present from the calculations in appreciable quantities in the gaseous phase are iron dichloride and manganese dichloride. In the low-temperatures zone and for low initial nitrogen contents, it result that the appearance of the liquid chlorides seems that partially inhibits the production of gaseous HCI. The highest deposition process efficiency calculated is obtained at a temperature 2 900°C and a N2/TiCI, ratios 2 0.7.